ParB Partition Proteins: Complex Formation and Spreading at Bacterial and Plasmid Centromeres - Funnell, Barbara E. (Frontiers in Molecular Biosciences, 2016)
In bacteria, active partition systems contribute to the faithful segregation of both chromosomes and low-copy-number plasmids. Each system depends on a site-specific DNA binding protein to recognize and assemble a partition complex at a centromere-like site, commonly called parS. Many plasmid and all chromosomal centromere-binding proteins are dimeric helix-turn-helix DNA binding proteins, which are commonly named ParB. Although the overall sequence conservation among ParBs is not high, the proteins share similar domain and functional organization, and they assemble into similar higher-order complexes. In vivo, ParBs “spread”; that is, DNA binding extends away from the parS site into the surrounding nonspecific DNA, a feature that reflects higher-order complex assembly. ParBs bridge and pair DNA at parS and nonspecific DNA sites. ParB dimers interact with each other via flexible conformations of an N-terminal region. This review will focus on the properties of the HTH centromere-binding protein, in light of recent experimental evidence and models that are adding to our understanding of how these proteins assemble into large and dynamic partition complexes at and around their specific DNA sites.